Impact of perceived social support on depression in Chinese rural‐to‐urban migrants: The mediating effects of loneliness and resilience. Issue 7 (23rd July 2019) - Liang, Dekuo; Teng, Mingjun; Xu, Dawei
Abstract: The present study aimed to examine whether loneliness and resilience played the roles of mediators on the relationship between perceived social support and depression. A total of 712 Chinese rural‐to‐urban migrants from Nanjing, who were measured with perceived social support, resilience, loneliness, and depression, participated in the study. Results indicated that perceived social support and resilience were negatively associated with depression. Loneliness was a significant and negative predictor for depression. In addition, we also revealed that resilience and loneliness partially mediated the relationship between perceived social support and depression. These findings might develop a better understanding of depression in the course of migration.